Pendidikan Islam Transdisipliner dan Sumber Daya Manusia di Madrasah Negeri Batu Bara - Fachruddin Azmi; Ismail MZ; Asrul Asrul; Suwastati Sagala; Nasrul Syakur Chaniago (Departement of Mathematics Education, 2023)
that it negates the refinement between general knowledge and the science of religion and all the sciences that are developed are realized to be interconnected between one another. The method used is the method of analysis discourse and content. The way a number of literature is analyzed and analyzed and well researched based on direction and purpose of the transdisciplinary concept. Apparently, in the context of education The Islamic transdisciplinary curriculum that must be developed must be holistic, namely could cover various problem existing and attached on man and development as a whole human resource and self-development. Man as a mysterious creature is not if only approached with/by one scientific discipline, it must be understood in a manner cross discipline science . Ability which expected achieved in Transdisciplinary Islamic education is the ability to see the world as a value system, each of which has different duties and functions different but permanent each other related. System connections this on Put it in frame faith and morals glorious.